CURRENT STATE OF THE PROBLEMS OF DISPOSAL OF DOMESTIC WASTE - Zhmur, Nataliia; Brusylo, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to analyze the current state of domestic waste disposal problems in Ukraine and the world, to determine the main causes of their occurrence and to propose solutions. Research methods: the work uses general scientific and special research methods, in particular: dialectical, historical, logical, systemic approaches, methods of analysis and synthesis, induction and deduction, comparative legal method. Results: the article highlights current issues of legal regulation of household waste disposal both in Ukraine and in other countries of the world. The main causes of problems with waste disposal are identified and ways to overcome them are proposed by improving the legislation, introducing the latest recycling technologies and raising the level of environmental awareness of citizens. Discussion: the problem of disposal of household waste is one of the most acute environmental problems of our time. The increase in the volume of waste generation due to the growth of consumption and urbanization, the insufficient level of processing and reuse of resources, as well as ineffective legislative regulation in this area lead to environmental pollution and a negative impact on human health. Researching this problem and finding ways to solve it is an extremely important task both for Ukraine and for the entire world community.